Application of Artificial Intelligence to Maximise Digital Marketing Effectivity on Instagram - Kurnianti, Dinni; Ifkari Safitri, Heida; Safitri, Indri (JURNAL DINAMIKA MANAJEMEN DAN BISNIS, 2024)
The research aims to investigate and analyze the application of Artificial Intelligence (AI) in improving the effectiveness of Digital Marketing strategies on the Instagram platform. The research focused on active Instagram users aged 18-34, as the main demographic group in the social media ecosystem. The study uses a qualitative research method with Structural Equation Modeling-Partial Least Squares (SEM-PLS) as an analysis framework to measure and validate the relationship between variables involved in the application of AI. The results are expected to provide in-depth insight into the crucial role of AI in improving the effectiveness of digital marketing strategies on Instagram, with significant implications for practitioners and researchers in this field.